Kompetensi 4C (creative thinking, critical thinking, communication, and collaboration) dalam pembelajaran Bahasa Arab era society 5.0 - Rahman, Linda Octaverina (Maliki Interdisciplinary Journal, 2023)
Learning Arabic has developed along with the development of technology, especially in the digital era, which is now known as the era of society 5.0. The purpose of this writing is to find out learning Arabic based on 4C competencies (creativity, critical thinking, communication, and collaboration) in the era of society 5.0. The research method used is a literature study using a descriptive approach and using a study study of the literature, journals from 2020 to 2023. The results of this research are, 1. Creativity: students are able to creatively produce, develop and implement ideas the idea is to make sentences with Arabic vocabulary and create easy-to-understand Arabic learning, 2. Critical Thinking: training students to search for the meaning of Arabic vocabulary through dictionaries and digital applications, 3. Communication: students can speak Arabic fluently with the guidance of the teacher at school or native speakers in YouTube content, tick-tok, and other applications, and 4. Collaboration: students are able to work together with group mates and appreciate the ideas of other groups through Arabic-based project assignments given by the teacher.